2020
DOI: 10.1016/j.giq.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the transparency of local government websites through a political market framework

Abstract: This paper contributes to the literature on government transparency by addressing the question of what drives the differences in local government levels of transparency. Our main objective is to ascertain whether transparency is mainly driven by the leadership, capacity and other political traits of the local governments themselves-"supply-side determinants"-or, rather, if it hinges on social, cultural and/or other local community factors ("demand-side" determinants). We test the hypotheses derived from this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
99
6
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(139 citation statements)
references
References 55 publications
(62 reference statements)
13
99
6
21
Order By: Relevance
“…Transparency empowers citizens in the government accountability process [90], engendering trust in government. Through the use of ICT technology, government information and decisions can be made public without any particular hindrance, increasing the culture of transparency [91]. Transparency is the focal point of citizens' trust in government [132], and decision transparency helps trust flourish.…”
Section: B Public Trust (Pt) To Intensify E-gov Iot Usage Behaviormentioning
confidence: 99%
“…Transparency empowers citizens in the government accountability process [90], engendering trust in government. Through the use of ICT technology, government information and decisions can be made public without any particular hindrance, increasing the culture of transparency [91]. Transparency is the focal point of citizens' trust in government [132], and decision transparency helps trust flourish.…”
Section: B Public Trust (Pt) To Intensify E-gov Iot Usage Behaviormentioning
confidence: 99%
“…They cover only 5 items related to financial transparency and show a very limited use of SM for financial reporting. Decisive reasons for fluctuations in levels of transparency have not been found (Bearfield & Bowman, 2017;Tavares & da Cruz, 2017), but population size, income per capita and political factors are usually significant in Spanish municipalities (Alcaide et al, 2017). A study analyzing Facebook use by the biggest local governments in Italy and Spain for information disclosure purposes (Guillamón et al, 2016) also found that population size and citizens' income level, together with the level of e-participation and indebtedness, influence the level of municipal transparency through SM.…”
Section: The Spanish Contextmentioning
confidence: 99%
“…Adding unemployment or debt per capita as explanatory variable has no relevant impact on our conclusions. Adding the average age of the municipal population (which Tavares and da Cruz forthcoming, have shown to be correlated with MTI) or the proportion of elderly people in the population has no impact either. Because the proportion of the youth population could be correlated with the importance attached to exam grades, we also controlled for this variable, but nothing changed.…”
Section: Resultsmentioning
confidence: 94%
“…For example, Arvate et al () show that, in Brazil, deficits are electorally punished in states with higher than average schooling years, while Bojar () shows that high‐status individuals (a measure that includes education) are less likely to punish deficit reductions or to reward spending increases. Furthermore, although existing evidence on the determinants of MTI for Portugal counters that hypothesis (Tavares and da Cruz forthcoming), one could even argue that government transparency is itself a consequence of an electorate with greater levels of education. Therefore, we also estimate models including a variable measuring the percentage of the population in each municipality with college education, also estimating its interaction with the fiscal performance variables.…”
Section: Data and Hypothesesmentioning
confidence: 98%